Chemically Twisted Superlattices of Two-dimensional Assemblies of Copper Nanoclusters - Das, Priya (My University, 2024)
The organization of molecules or atoms in a hierarchical manner leads to the formation of complex superstructures with enhanced properties and functionalities, resulting in superior performance when compared to mono-morphological units. Researchers have been motivated by the impact of these achievements to explore the design and fabrication of materials with hierarchical assembly at the nanoscale level. In this regard, research on the hierarchical assembly of two-dimensional (2D) nanomaterials has led to several exciting discoveries in various fields such as energy storage, optoelectronic devices, chemical sensors, catalytic performance, membranes, and solar cells.
Chattopadhyay, Arun
Keywords: Physical Chemistry; Materials Chemistry; 2D Materials; Moire Superlattices